Pengaruh Atribut Produk, Ketidak Puasan Konsumen, Dan Mencari Variasi Terhadap Perilaku Perpindahan Merk Smartphone Di Kota Metro (Studi Pada Mahasiswa Manajemen FEB UM Metro Angkatan 2017) - Yuda, Ladi Arma; Nasikah, Durotun (Jurnal Manajemen DIVERSIFIKASI, 2022)
Nowadays, a brand can no longer be said to be a part of a product. Therefore, the brand must be maintained if it is managed properly. Such brand management activities must be viewed as valuable activities for the company. Types of consumer behavior in purchasing decisions that tend to make brand shifts are limited and inertia decision making. The purpose of this study is to determine whether product attributes, consumer dissatisfaction, and looking for variations simultaneously influence the behavior of smartphone brand switching. In this study using primary data and secondary data, the research method used was the sampling technique using the Slovin formula, namely management students of the faculty of economics and business, Muhammadiyah University of Metro class of 2017, with a total sample of 114 people. The data analysis technique used is validity test, reliability test, normality test, linearity test. Testing the analysis model in this study using multiple linear regression analysis, T test, F test and R determination. Based on the results of research using the T test, it is found that product attributes have a significant and significant effect on the behavior of smartphone brand switching, consumer dissatisfaction has no and insignificant effect on the behavior of smartphone brand switching, and looking for variations has an effect and is significant on the behavior of smartphone brand switching. From the product attribute F test, consumer dissatisfaction and looking for variations together have an effect and are significant on the behavior of smartphone brand switching. Keywords- Product Attributes, Consumer Dissatisfaction, Seeking Variation and Brand Change Behavior